ANALYSIS OF FIXED ASSET MANAGEMENT IN FINANCIAL STATEMENTS: A CASE STUDY OF SERDANG BEDAGAI REGENCY 2023 - Lisbetria Simamora; Syakira Faira Hutasuhut; Iskandar Muda (JITAA : Journal Of International Taxation, Accounting And Auditing, 2025)
Fixed assets are an important component in a region's financial statements and balance sheets that will prove the wealth of the local government. This research is based on secondary data obtained from the Notes on the Financial Statements of Serdang Bedagai Regency for 2023. From the results of the research, fixed assets in Serdang Bedagai Regency have met the 2019 Government Accountability Standards (SAP), but several indications of problems were found such as the value of Construction in Work with a value of 0 or completed in 2023. This is unusual compared to reports in the field. Because in 2023 there is still work that is still ongoing and has not been completed, supported by some of the evidence listed in the research. In addition, the large value of damaged assets shows that the Serdang Bedagai Regency Government is lacking in maintaining asset maintenance. This research identifies fixed assets and hopes that the results of this research can be an input for the government of Serdang Bedagai Regency, especially in the fixed asset category with the aim of improving the quality of financial statements.